Protein Structural Characterization Using Electron Transfer Dissociation and Hydrogen Exchange-Mass Spectrometry - Rupam Bhattacharjee; Jayant Udgaonkar (Bio-Protocol)
Intermediate states are often populated during the folding and unfolding reactions of a protein, and their detection is very challenging as they form transiently. Structural characterization of these short-lived intermediate species is difficult as it requires high-resolution methodologies. Hydrogen exchange-mass spectrometry (HX-MS) can identify and yield direct structural information on folding and unfolding intermediates, as well as information about the cooperativity of the folding or unfolding processes. The mass distributions of intact protein molecules are obtained first to determine their exchange pattern. Then, segment-specific structural information is obtained by analyzing the fragments of the protein. Enzymatic digestion is widely used with HX to determine the sequence-specific structural changes that occur to the protein during folding or unfolding. However, if a protein is an inhibitor of the protease, then alternative methodologies are required. Using electron transfer dissociation (ETD), it is possible to fragment the protein inside a mass spectrometer, and segment-specific structural changes occurring during the folding and unfolding process can be determined. In the case of HX-ETD-MS, protein molecules are first allowed to undergo HX, followed by their fragmentation. Deuterium retention in each fragment is measured. Very little, if any, scrambling of deuterium across fragments occurs during ETD-enabled fragmentation; hence, there is little scope for misinterpretation of the HX data.